DIDMOAD syndrome with megacystis and megaureter. Issue 731 (September 1986) - Chu, P.; Staff, W. G.; Morris, J. A.; Polak, J. M.
Abstract : A case of DIDMOAD syndrome (diabetes insipidus, diabetes mellitus, optic atrophy and nerve deafness) is described. There was unusually severe urinary tract dilatation which led to an ileal conduit diversion. Immunohistological study of the bladder wall and ureter revealed a marked diminution in nerve fibres, which may have been primary or secondary to the muscle hypertrophy. The possible pathogenesis of the urinary tract dilatation is discussed in relation to this finding.